2017
DOI: 10.1007/s12040-017-0858-3
|View full text |Cite
|
Sign up to set email alerts
|

Run-off analyses using isotopes and hydrochemistry in Yushugou River basin, eastern Tianshan Mountains

Abstract: Yushugou River basin of East Tianshan Mountains receives water from melting glaciers. In recent years, the glaciers retreated strongly due to global warming which intensified the water cycle in the river basin. For this reason, the relation of water bodies based on hydrochemistry and isotope in the summer flood was carried out. Hydrochemistry research showed that there was frequent hydraulic interaction between river water and groundwater. Studying the isotopes and Cl − of river water, glacier meltwater, groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Groundwater discharges often make up a substantial share of surface flows (e.g., Bolduc et al, ; Calvi et al, ; Cao et al, ; Cook et al, ; England et al, ; Foks et al, ; Fritz et al, ; Genereux et al, ; Georgek et al, ; Hooper et al, ; Le Maitre & Colvin, ; Ma et al, ; Martinez et al, ; Pinder & Jones, ; Sklash & Farvolden, ; Smerdon et al, ; Smith et al, ; Tague et al, , ; Tague & Grant, , ; Turner et al, ; Walvoord & Striegl, ; Wang, Li, & Jiang, ; Zimmer et al, ). Groundwater discharges sustain streamflow even when rain is not falling and snow is not melting, influencing riverine solute loads, moderating stream temperatures, and creating perennial aquatic habitat (e.g., Bertrand et al, ; Boulton & Hancock, ; Briggs et al, ; Hayashi & Rosenberry, ; Irvine et al, ; Jefferson et al, ; Kløve et al, ; Kurylyk et al, ; McGuire et al, ; O'Driscoll & DeWalle, ; Petts et al, ; Poff & Zimmerman, ; Rose et al, ; Sear et al, ; Wood et al, , ).…”
Section: Groundwater Discharges To Riversmentioning
confidence: 99%
“…Groundwater discharges often make up a substantial share of surface flows (e.g., Bolduc et al, ; Calvi et al, ; Cao et al, ; Cook et al, ; England et al, ; Foks et al, ; Fritz et al, ; Genereux et al, ; Georgek et al, ; Hooper et al, ; Le Maitre & Colvin, ; Ma et al, ; Martinez et al, ; Pinder & Jones, ; Sklash & Farvolden, ; Smerdon et al, ; Smith et al, ; Tague et al, , ; Tague & Grant, , ; Turner et al, ; Walvoord & Striegl, ; Wang, Li, & Jiang, ; Zimmer et al, ). Groundwater discharges sustain streamflow even when rain is not falling and snow is not melting, influencing riverine solute loads, moderating stream temperatures, and creating perennial aquatic habitat (e.g., Bertrand et al, ; Boulton & Hancock, ; Briggs et al, ; Hayashi & Rosenberry, ; Irvine et al, ; Jefferson et al, ; Kløve et al, ; Kurylyk et al, ; McGuire et al, ; O'Driscoll & DeWalle, ; Petts et al, ; Poff & Zimmerman, ; Rose et al, ; Sear et al, ; Wood et al, , ).…”
Section: Groundwater Discharges To Riversmentioning
confidence: 99%
“…Subsequent work with geochemical tracers has geographically expanded our understanding of groundwater discharge to different mountain hydrological regimes in the Rockies (Carroll et al, 2018; Cowie et al, 2017; Frisbee et al, 2011; Liu et al, 2008), Andes (Baraer et al, 2009, 2015; Saberi et al, 2019), Alps (Engel et al, 2016; Schmieder, Garvelmann, Marke, & Strasser, 2018), Himalayas (Jeelani, Bhat, & Shivanna, 2010; Maurya et al, 2011; Williams et al, 2016; A. M. Wilson et al, 2016), Tianshan Mountains (Wang et al, 2017), and Canadian North (Carey et al, 2013). For example, in Wolf Creek, Yukon, Canada (a low‐ to mid‐altitude mountain watershed with alpine characteristics), (Carey et al, 2013) showed that water stored in near‐surface soils within the catchment dominated the snowmelt hydrograph based on a multi‐year combination of isotope and major ion data.…”
Section: Quantifying Groundwater Contribution To High Mountain Riversmentioning
confidence: 99%
“…Through tracer studies, even glacierized environments were shown to have substantial groundwater inflow to rivers. Baraer et al (2015) found that groundwater contributes 24-80% of dry season stream discharge in four proglacial valleys of the Cordillera Blanca in the northern Peruvian Andes, while Wang et al (2017) found that groundwater contributed 38% of streamflow in a glacierized watershed of the Tianshan Mountains in China. More recent work has increased the spatial and temporal resolution of results, examined fine-scale groundwater flow paths and made use of new tracers such as chloride isotopes (Shaw et al, 2014), sulfur isotopes (Urióstegui, Bibby, Esser, & Clark, 2017), and dissolved noble gasses (Gleeson et al, 2018).…”
Section: Geochemical Tracersmentioning
confidence: 99%
“…Processes and reactions during groundwater recharge, storage and discharge, including mixing, evaporation, seasonal variations and high-temperature rock-groundwater interactions, can be characterised by isotopes [105]. δ 2 H and δ 18 O stable isotopes are frequently applied in groundwater studies and also for revealing surface water-groundwater interactions [106][107][108][109].…”
Section: Stable Isotope Analysismentioning
confidence: 99%